Funcionarios de Oficina de Operaciones. (UNED, 2025)
Luis Carlos Monge, Teddy Chan, Marvin Campos, Marcial Prado, Miguel Bejarano, Alejandro Cerdas, Walter Amey, María Elena Benavides, María Isabel Esquivel, Roxana Cubero y Esperanza Valladares